2020
DOI: 10.1007/s10064-020-01863-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel landslide susceptibility mapping portrayed by OA-HD and K-medoids clustering algorithms

Abstract: Because of the strong dependence on the values for the input parameters and the cluster shape, as well as the difficulties in quantifying the precipitation in constructing landslide susceptibility maps by employing existing clustering algorithms, we propose a novel method based on an Ordering Points to Identify the Clustering Structure (OPTICS) algorithm using the Hausdorff distance (OA-HD). The OA-HD algorithm distributes mapping units into many subclasses with similar characteristic values for topography and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…e merging process based on a dynamic model facilitates the discovery of natural and homogeneous clusters and applies to all types of data as long as a similarity function is specified [51]. To its advantage, the Chameleon algorithm is a usersupplied model, static independent, as well as adapting to the internal characteristics of the clusters of being independent of the initial partitions, as well as insensitive to noise and outliers [44]; thus, we used Chameleon algorithm to assess the landslide susceptibility. In general, for landslide susceptibility assessment using the clustering algorithm, an object is regarded as a grid.…”
Section: Chameleon Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…e merging process based on a dynamic model facilitates the discovery of natural and homogeneous clusters and applies to all types of data as long as a similarity function is specified [51]. To its advantage, the Chameleon algorithm is a usersupplied model, static independent, as well as adapting to the internal characteristics of the clusters of being independent of the initial partitions, as well as insensitive to noise and outliers [44]; thus, we used Chameleon algorithm to assess the landslide susceptibility. In general, for landslide susceptibility assessment using the clustering algorithm, an object is regarded as a grid.…”
Section: Chameleon Algorithmmentioning
confidence: 99%
“…Clustering analysis algorithms classify sets of objects (grids) into groups that are more similar to each other than they are to objects in other clusters (groups) [44]. is process is conducted by primitive observation with little or no prior knowledge; that is, it is unsupervised learning.…”
Section: Introductionmentioning
confidence: 99%
“…Because of these limitations, SL methods may not be applicable where there are a limited number of labeled samples as they are not always easy to obtain and may be expensive to acquire in abundance through image interpretation and site surveying, especially in a large study area. USL-based approaches are applied and have contributed to improving the implementation and the accuracy of LSM in such situations (Lei et al, 2018;Hu et al, 2021;Yimin et al, 2021;Mao et al, 2022;Su et al, 2022;Liu et al, 2023). USL-based methods such as clustering can be used to map the susceptibility areas, as they can identify the underlying structures in unlabeled datasets, hence, do not require data with predefined labels, and do not involve a training process during their implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Over decades, these methods have been widely used in other fields such as marketing research, pattern recognition, and image processing, but very rarely explored in LSM studies (Huang et al, 2020;Su et al, 2022). In recent years, making use of the advantages of these methods, some landslide researchers have also shown interest and conducted LSM studies using these methods (Wan et al, 2015;Wang et al, 2017;Hu et al, 2019;Mao et al, 2021a;Mao et al, 2021b;Hu et al, 2021;Pokharel et al, 2021;Yimin et al, 2021;Mao et al, 2022). From the analysis of these studies and other traditional clustering algorithms, some limitations were observed: the inability to detect subclasses with arbitrary shapes, sensitivity to noise, inability to perform well in large study areas with large datasets, and principally a standard method to process the uncertain data (rainfall) has not being obtained yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation